2 exercises in simple regression - Geary, R.C. (Economic & Social Studies, 1972)
While the two exercises are independent in that they purport to answer separate questions, methodologically they are very similar. They both compare the efficiency of different methods of estimation of parameters by the familiar method of ratio F of variances of estimate, stochastically decisive, under very general conditions, when number of observations T tends towards infinity.
Keywords: Simple Regression